2001
DOI: 10.1073/pnas.051629798
|View full text |Cite
|
Sign up to set email alerts
|

Localization and regulation of GLUTx1 glucose transporter in the hippocampus of streptozotocin diabetic rats

Abstract: We describe the localization of the recently identified glucose transporter GLUTx1 and the regulation of GLUTx1 in the hippocampus of diabetic and control rats. GLUTx1 mRNA and protein exhibit a unique distribution when compared with other glucose transporter isoforms expressed in the rat hippocampus. In particular, GLUTx1 mRNA was detected in hippocampal pyramidal neurons and granule neurons of the dentate gyrus as well as in nonprincipal neurons. With immunohistochemistry, GLUTx1 protein expression is limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 35 publications
3
64
0
1
Order By: Relevance
“…non-diabetic) animals, hippocampus-dependent learning is correlated with a decrease in extracellular glucose levels, and intrahippocampal injection of glucose improves performance 41 . No studies to date have reported an effect of diabetes on learning-induced changes in hippocampal glucose metabolism, but alterations in basal hippocampal glucose transporter expression have been demonstrated in diabetic animals 42 . While we observed no difference in glucose levels in whole hippocampal homogenates from insulin resistant mice or insulin deficient rats, our results do not preclude a role for corticosterone in modulating the diabetes-induced alterations in hippocampal glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…non-diabetic) animals, hippocampus-dependent learning is correlated with a decrease in extracellular glucose levels, and intrahippocampal injection of glucose improves performance 41 . No studies to date have reported an effect of diabetes on learning-induced changes in hippocampal glucose metabolism, but alterations in basal hippocampal glucose transporter expression have been demonstrated in diabetic animals 42 . While we observed no difference in glucose levels in whole hippocampal homogenates from insulin resistant mice or insulin deficient rats, our results do not preclude a role for corticosterone in modulating the diabetes-induced alterations in hippocampal glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, glucose transport is probably not a key regulator of neuronal glucosensing because the predominant neuronal transporter, GLUT-3, is ubiquitous and saturated at physiological brain glucose concentrations (34). Other brain glucose transporters (GLUT-1, -2, -4, and -8) have either inappropriate anatomic or cell type localizations (35)(36)(37)(38).…”
Section: Diabetes Vol 51 July 2002mentioning
confidence: 99%
“…GLUT8 mRNA is widely expressed in tissues including brain (cerebellum, brainstem, hippocampus, and hypothalamus), adrenal gland, spleen, brown adipose tissue, white adipose tissue, placenta, muscle, heart, and liver. The concentration of GLUT8 mRNA is greatest in testis [132][133][134][135][136] where its expression has been linked to circulating gonadotropins. Estrogen treatment suppressed GLUT8 expression in testis [133], and no expression of GLUT8 mRNA could be detected in testis of prepubertal (12 days) mice.…”
Section: Glut8mentioning
confidence: 99%
“…More recently GLUT8 was immunolocalized to the acrosome in sperm suggesting that GLUT8 may be important in maintaining reproductive function and/or fertility [138]. Utilizing immunohistochemistry and emulsion autoradiographic analysis, GLUT8 has been detected in rat hippocampal neurons and localized to the cytoplasm of neuronal cell bodies [135]. The absence of other glucose transporters and increased expression of GLUT8 mRNA in STZ diabetes in this subset of neurons highlighted a possible contribution of GLUT8 in supporting glucose requirements of hippocampal neuronal cell bodies and their cognitive function [135].…”
Section: Glut8mentioning
confidence: 99%
See 1 more Smart Citation